2011
DOI: 10.1007/s10620-011-1783-y
|View full text |Cite
|
Sign up to set email alerts
|

Prodromal Irritable Bowel Syndrome May Be Responsible for Delays in Diagnosis in Patients Presenting with Unrecognized Crohn’s Disease and Celiac Disease, but Not Ulcerative Colitis

Abstract: This is the first study to make direct comparisons of prodrome periods between celiac disease and IBD. Prodrome duration in celiac disease is significantly longer and more often characterized by P-IBS than IBD. In celiac disease and CD, P-IBS increases prodrome duration. This may represent a failure to understand the overlap between IBS and celiac disease/IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 19 publications
2
25
0
Order By: Relevance
“…The accuracy established here is similar to previous published data [20][21][22]. There is a significant need for noninvasive, safe, resource-conscious modalities of accurately detecting inflammation in symptomatic patients, as symptoms alone do not accurately reflect inflammatory disease activity and incorrect diagnosis can delay appropriate management of IBD [23,24]. Ultrasound has been shown to significantly impact clinical decisions, when used at the bedside [25].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The accuracy established here is similar to previous published data [20][21][22]. There is a significant need for noninvasive, safe, resource-conscious modalities of accurately detecting inflammation in symptomatic patients, as symptoms alone do not accurately reflect inflammatory disease activity and incorrect diagnosis can delay appropriate management of IBD [23,24]. Ultrasound has been shown to significantly impact clinical decisions, when used at the bedside [25].…”
Section: Discussionsupporting
confidence: 82%
“…In this study, CRP was not suggestive of more severe disease either sonographically or endoscopically, illustrating, even in this small sample, limitations with using CRP as a guide for the need for endoscopy. Given current wait-times for nonurgent endoscopy, inappropriate delays may result as a consequence of false-negative results of currently available tests [24]. Thus, a widely available, accurate set of clinical tools that would include noninvasive US may guide the appropriate use of diagnostic endoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Delay in diagnosis has been reported previously in the literature regarding both Crohn's disease and coeliac disease 11–13. Regarding coeliac disease, studies suggest that this delay is usually longer than for IBD, with an average time of between 5 and 10 years between initial presentation with abdominal pain and diagnosis 12 14 15. Abdominal pain is part of the presentation in as many as 72% of children with Crohn's disease,11 so it is possible that in some of these cases, the index presentation with abdominal pain was indeed a first presentation of Crohn's disease or other bowel pathology.…”
Section: Discussionmentioning
confidence: 99%
“…It has been stated that patients with likely or possible pre-existing IBS were more likely to experience a longer, although not statistically significant, diagnostic delay of IBD [4]. Moreover, Pimentel et al [5] asserted in their work that the duration of the prodromal period of the disease in CD patients with no IBS symptoms is indeed reduced, although not statistically significant, compared to those CD patients with IBS symptoms; by contrast, Barratt et al showed that the duration of the prodromal CD symptoms is increased in patients with prodromal IBS symptoms at onset [2]. Further investigations are required to clarify this aspect.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have shown that the time interval between the initial onset of symptoms secondary to CD and formal diagnosis can vary from 5 months to 11 years [1][2][3][4][5][6]. Interestingly, some of these studies have highlighted that >25% of patients were diagnosed beyond 24 months from the initial presentation.…”
Section: Introductionmentioning
confidence: 99%